Total parietal peritonectomy in primary debulking surgery for advanced ovarian cancer - Kota Yokosu; Hiroshi Tanabe; Shogo Nomura; Hirokazu Ozone; Motoaki Saito; Hirokuni Takano; Aikou Okamoto (Elsevier, 2021)
The object of this study is to evaluate the clinical safety and efficacy of total parietal peritonectomy (TPP) in primary debulking surgery (PDS) for advanced ovarian cancer. This retrospective single-center study analyzed 16 patients with FIGO stages IIIC-IVB epithelial ovarian cancer who underwent TPP in PDS and achieved macroscopically complete resection between April 2015 and June 2016. The median age of 16 patients was 52.5 years old. 12 were in stage IIIC and 4 were in stage IV.Regarding intraoperative complications, unintended diaphragm perforation was observed in two patients. Regarding postoperative complications (Clavien-Dindo classification grade 3-5) before the adjuvant chemotherapy, lymph cysts occured in 3 patients, intra-abdominal abscess in 3, ileus in 2, pancreatic fistula in 1 and temporary kidney failure in 1. Regarding postoperative complications (grade 3-5) after the initiation of adjuvant chemotherapy, diaphragmatic hernia occured in 1 patient, ileus in 2 and intra-abdominal abscess in 2. Except 1 patient who relapsed approximately one month from surgery and died, the other 15 patients overcamed complications and recovered without problems in daily life. This analysis was conducted 3 years after all patients underwent PDS, with the 3-year progression-free and overall survival of 62.5% (95% confidence interval [CI], 34.9-81.1) and 87.5% (95 %CI, 58.6-96.7), respectively.Based on the above results, TPP in PDS may improve the prognosis compared to previous reports such as LION trial. On the other hand, complications may increase. Therefore, further studies are necessary on its safety and efficacy.